Lutra canadensis - James H. Honacki; Kenneth E. Kinman; James W. Koeppl (Alien Press, Inc. & The Association of Systematics Collections, 1982)
Lutra canadensis (Schreber, 1776). Saugethiere, pl. 126 b. TYPE LOCALITY: Eastern Canada. DISTRIBUTION: North America south to Arizona, Texas, and Florida (U.S.A.). COMMENT: Includes mira; see Van Zyll de Jong, 1972, Life Sei. Contrib. R. Ont. Mus., 80:1 -104. PROTECTED STATUS: CITES - Appendix II as Lutrinae. ISIS NUMBER: 5301412004023001001 as Lontra canadensis. Published as part of James H. Honacki, Kenneth E. Kinman & James W. Koeppl, 1982, Order Carnivora, pp. 244-289 in Mammal Species of the World (1 st Edition), Lawrence, Kansas, USA :Alien Press, Inc. & The Association of Systematics Collections on page 258, DOI: 10.5281/zenodo.7352980